Accessory and Expiratory Muscles Activation During Spontaneous Breathing Trial: A Physiological Study by Surface Electromyography - Pozzi, Matteo; Rezoagli, Emanuele; Bronco, Alfio; Rabboni, Francesca; Grasselli, Giacomo; Foti, Giuseppe; Bellani, Giacomo (Frontiers in Medicine, 2022)
Background The physiological and prognostic significance of accessory and expiratory muscles activation is unknown during a Spontaneous Breathing Trial (SBT). We hypothesized that, in patients experiencing weaning failure, accessory and expiratory muscles are activated to cope with an increased respiratory workload. Purpose To describe accessory and expiratory muscle activation non-invasively by surface electromyography (sEMG) during a SBT and to assess differences in electrical activity (EA) of the inspiratory and expiratory muscles in successful versus failing weaning patients. Methods: Intubated patients on mechanical ventilation for more than 48 hours undergoing a SBT were enrolled in a Medical and Surgical third level ICU of a University Teaching Hospital. Baseline characteristics and physiological variables were recorded in a crossover physiologic prospective clinical study. Results: Of 37 critically ill mechanically ventilated patients, 29 (78%) successfully passed the SBT. Rapid shallow breathing index (RSBI) was higher in patients who failed SBT compared to successfully weaned patients at baseline and overtime (group-by-time interaction p<0.001). EA of both diaphragm (EAdisurf) and of accessory muscles (ACCsurf) was higher in failure patients compared to success (group-by-time interaction p=0.0174 and p<0.001, respectively). EA of expiratory muscles (ESPsurf) during SBT increased more in failure than in weaned patients (group-by-time interaction p<0.0001). Conclusion Non-invasive respiratory muscles monitoring by sEMG was feasible during SBT. Respiratory muscles EA increased during SBT, regardless SBT outcome, and patients who failed the SBT had a higher increase of all inspiratory muscles EA compared to patients who passed the SBT. Recruitment of expiratory muscles – as quantified by sEMG – is associated with SBT failure.